Health Status of Rural Girls - Madhuri Inamdar; Sameer Inamdar; N. L. Sachdeva (National Journal of Community Medicine, 2011)
Background- In most of the developing countries, the girl child is ill fed and undernourished. 1 Quite often the root cause of malnutrition among girls is not so much the lack of food as the lack of access to food. Thus undernourished girls who grow into undernourished women perpetuate the intergenerational undernourishment cycle.2